The Role of Cerebral Hypercarbia in the Induction of the Near-Death Experience - A Shaw Nigel (Journal of Nervous System and Physiological Phenomena, 2024)
The near-death experience (NDE) is an altered state of consciousness which arises when a person is critically ill or injured and possibly clinically dead. It should not be conflated with other mental events such as the deathbed vision or the fear or anticipation of death. Many believe that the NDE represents a genuine paranormal phenomenon providing a glimpse of an otherworldly existence and proof of an afterlife. Those who are skeptical of such a survivalist or supernatural interpretation have long pointed out that the core components of the NDE can be readily simulated with a variety of states, conditions and agents. In this conception, the NDE is reduced to no more or less than an extraordinarily complex hallucination. Since its rediscovery in the 1970s, multiple, often ingenious, attempts have been made to account for the NDE in such naturalistic or neuroscientific terms. None has so far proven completely satisfactory. One of the oldest, least considered but still promising is the CO2 theory which argues that a hypercarbic brain is a necessary precursor for the induction of a NDE. Supportive evidence that CO2 does play a pivotal role in the generation of the NDE can be gathered from diverse sources. These include: 1. measurement of blood gases; 2. Meduna’s now abandoned CO2 therapy; 3. analysis of the very limited number of pathophysiological conditions underlying the NDE; 4. recent discoveries of the role of 5-HT neurons in the central respiratory system. A model is proposed in which CO2 molecules are considered to be functionally equivalent to those of the classical hallucinogens (LSD, mescaline, psilocybin, dimethyltryptamine). These agents can mimic the phenomenology of the NDE with remarkable fidelity. What is still missing from any such explanation is the long-sought transduction mechanism which converts physical events into mental ones. This is a generic problem which confronts all attempts to explain the neurogenesis of mystical, psychedelic or visionary activity.
Keywords: Carbogen therapy